ATP6V1H facilitates osteogenic differentiation in MC3T3-E1 cells via Akt/GSK3β signaling pathway. (3rd April 2019) - Jiang, Fusong; Shan, Haojie; Pan, Chenhao; Zhou, Zubin; Cui, Keze; Chen, Yuanliang; Zhong, Haibo; Lin, Zhibin; Wang, Nan; Yan, Liang; Yu, Xiaowei
ABSTRACT: Type 2 diabetes mellitus (T2DM) accounts for approximately 90% of all diabetic patients, and osteoporosis is one of the complications during T2DM process. ATP6V1H (V-type proton ATPase subunit H) displays crucial roles in inhibiting bone loss, but its role in osteogenic differentiation remains unknown. Therefore in this study, we aimed to explore the biological role of ATP6V1H in osteogenic differentiation. OM (osteogenic medium) and HG (high glucose and free fatty acids) were used to induce the MC3T3-E1 cells into osteogenic differentiation in a T2DM simulating environment. CCK8 assay was used to detect cell viability. Alizarin Red staining was used to detect the influence of ATP6V1H on osteogenic differentiation. ATP6V1H expression increased in OM-MC3T3-E1 cells, while decreased in OM+HG-MC3T3-E1 cells. ATP6V1H promoted osteogenic differentiation of OM+HG-MC3T3-E1 cells. Overexpression of ATP6V1H inhibited Akt/GSK3β signaling pathway, while knockdown of ATP6V1H promoted Akt/GSK3β signaling pathway. ATP6V1H overexpression promoted osteogenic differentiation of OM+HG-MC3T3-E1 cells. The role of ATP6V1H in osteogenic differentiation in a T2DM simulating environment involved in Akt/GSK3β signaling pathway. These data demonstrated that ATP6V1H could serve as a potential target for osteogenic differentiation in a T2DM simulating environment.